3. UPAYA AMERIKA SERIKAT DALAM MENANGANI COUNTERFEIT GOODS DARI CHINA TAHUN 2011-2014 - Merry Elma Lordex Waruwu; Tri Cahyo Utomo; Shary Charlotte Pattipelohy (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
In the era of globalization, trade liberalization characterized by problems of counterfeitgoods. Definition of counterfeiting according to the International Trademark Association isa practice of manufacturing goods which are low in quality, and sold under a famous brand,without having a license, and without supervision of a brand and patent owner of the goods.Counterfeit goods activity is not only on the production process, but also on the stage ofdistribution, and import-export process. Counterfeiting is closely related to IPR theft andbecame a global problem. Therefore, the United States as the country with the biggest IPRbasedindustries in the world, it is necessary to eradicate the source of counterfeit goodsfrom China. This study was conducted to measure the effectiveness of the efforts made bythe United States, so it can be a guide to the establishment of policies and strategies forachieve the desired results. In this research, the authors encountered several limitationsrelated to operating results, the result of criminal cases, as well as the lack ofunderstanding of U.S. citizen related to counterfeit goods. This type of research isqualitative descriptive study, in which the analysis is done by collecting data throughlibrary research by using books, journals, government documents, and other writtensources. Comprehension of this research was formed by theory of neo-realism and theoryof effectiveness by William N. Dunn. Thus it is capable to explain the limitations of theresults that have been done by the United States.